Costs and drivers of helminth parasite infection in wild female baboons. Issue 7 (14th May 2019) - Akinyi, Mercy Y.; Jansen, David; Habig, Bobby; Gesquiere, Laurence R.; Alberts, Susan C.; Archie, Elizabeth A.
Abstract: Helminth parasites can have wide‐ranging, detrimental effects on host reproduction and survival. These effects are best documented in humans and domestic animals, while only a few studies in wild mammals have identified both the forces that drive helminth infection risk and their costs to individual fitness. Working in a well‐studied population of wild baboons ( Papio cynocephalus ) in the Amboseli ecosystem in Kenya, we pursued two goals, to (a) examine the costs of helminth infections in terms of female fertility and glucocorticoid hormone levels and (b) test how processes operating at multiple scales—from individual hosts to social groups and the population at large—work together to predict variation in female infection risk. To accomplish these goals, we measured helminth parasite burdens in 745 faecal samples collected over 5 years from 122 female baboons. We combine these data with detailed observations of host environments, social behaviours, hormone levels and interbirth intervals (IBIs). We found that helminths are costly to female fertility: females infected with more diverse parasite communities (i.e., higher parasite richness) exhibited longer IBIs than females infected by fewer parasite taxa. We also found that females exhibiting high Trichuris trichiura egg counts also had high glucocorticoid levels. Female infection risk was best predicted by factors at the host, social group and population level: females facing the highest risk were old, socially isolated, living in dry conditions and infected with other helminths. Our results provide an unusually holistic understanding of the factors that contribute to inter‐individual differences in parasite infection, and they contribute to just a handful of studies linking helminths to host fitness in wild mammals. Abstract : Working in a well‐studied population of wild baboons ( Papio cynocephalus ) in the Amboseli ecosystem in Kenya, the authors pursued two goals, to (a) examine the costs of helminth infections in terms of female fertility and glucocorticoid hormone levels and (b) test how processes operating at multiple scales—from individual hosts to social groups and the population at large—work together to predict variation in female infection risk. Photograph credit: Elizabeth Archie.